1969
DOI: 10.1109/proc.1969.7158
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of results of explorer XXXI direct measurement probes

Abstract: Intercomparison measurements of the major ionospheric parameters of ion and electron density and temperature and ionic species made by direct measurement probes on the Explorer XXXl satellite are presented. Plasma density results are compared with simultaneous data from the Alouette II satellite. Probe results are from the following experiments: planar ion trap, planar electron trap, cylindrical electrostatic probes, high resolution magnetic ion mass spectrometer, planar Langmuir plate, and spherical ion probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…The uncertainty in the measurement of electron temperature is a function of signal current, but typically an error bar of order f 100°K is appropriate. There is good agreement with other measurements [4]. A sensitivity limit is introduced by the need to correct for residual signal currents which are partly plasma induced and partly instrumental and at concentrations below about 500/cm3 this causes a serious degradation in accuracy.…”
Section: The Measurement Of Electron Temperaturesupporting
confidence: 75%
“…The uncertainty in the measurement of electron temperature is a function of signal current, but typically an error bar of order f 100°K is appropriate. There is good agreement with other measurements [4]. A sensitivity limit is introduced by the need to correct for residual signal currents which are partly plasma induced and partly instrumental and at concentrations below about 500/cm3 this causes a serious degradation in accuracy.…”
Section: The Measurement Of Electron Temperaturesupporting
confidence: 75%
“…When the probe is forward looking, however, reliable electron temperatures T, can be obtained and these are in good agreement with the other T, measurements made on Explorer XXXI [5]. Small-scale variations in electron temperature appear tobe common and are not yet explained.…”
Section: Introductionsupporting
confidence: 66%
“…The Alouette I [4] and Alouette I1 [ 5 ] instruments are of the swept-frequency type, where the sounding frequency is gradually increased so that each pulse is slightly higher in frequency than the preceding pulse. They produce ionograms showing the delay of the received signals as a function of frequency under nearly constant plasma conditions.…”
Section: Abstract-thementioning
confidence: 99%
“…The spherical probe is operated in an ac mode which we have seen also gives lower electron tempera tures. Donley et al (1969,) concluded that the plane probe T. values are in better general agreement with incoherent-scatter results which were however not taken simultaneously. Subsequently simultaneous results were obtained for the St. Santin and Malvern incoherent scatter stations which provide strong support for the spherical probe results.…”
Section: Indirect Determinations Of Plasma Temperaturementioning
confidence: 69%